Optimal fractionation of preoperative radiotherapy and timing to surgery for rectal cancer (Stockholm III): a multicentre, randomised, non-blinded, phase 3, non-inferiority trial. Issue 3 (March 2017) - Erlandsson, Johan; Holm, Torbjörn; Pettersson, David; Berglund, Åke; Cedermark, Björn; Radu, Calin; Johansson, Hemming; Machado, Mikael; Hjern, Fredrik; Hallböök, Olof; Syk, Ingvar; Glimelius, Bengt; et al.
Summary: Background: Radiotherapy reduces the risk of local recurrence in rectal cancer. However, the optimal radiotherapy fractionation and interval between radiotherapy and surgery is still under debate. We aimed to study recurrence in patients randomised between three different radiotherapy regimens with respect to fractionation and time to surgery. Methods: In this multicentre, randomised, non-blinded, phase 3, non-inferiority trial (Stockholm III), all patients with a biopsy-proven adenocarcinoma of the rectum, without signs of non-resectability or distant metastases, without severe cardiovascular comorbidity, and planned for an abdominal resection from 18 Swedish hospitals were eligible. Participants were randomly assigned with permuted blocks, stratified by participating centre, to receive either 5 × 5 Gy radiation dose with surgery within 1 week (short-course radiotherapy) or after 4–8 weeks (short-course radiotherapy with delay) or 25 × 2 Gy radiation dose with surgery after 4–8 weeks (long-course radiotherapy with delay). After a protocol amendment, randomisation could include all three treatments or just the two short-course radiotherapy treatments, per hospital preference. The primary endpoint was time to local recurrence calculated from the date of randomisation to the date of local recurrence. Comparisons between treatment groups were deemed non-inferior if the upper limit of a double-sided 90% CI for the hazard ratio (HR) did not exceed 1·7. Patients were analysed according to intention to treat for all endpoints. This study is registered with ClinicalTrials.gov, number NCT00904813 . Findings: Between Oct 5, 1998, and Jan 31, 2013, 840 patients were recruited and randomised; 385 patients in the three-arm randomisation, of whom 129 patients were randomly assigned to short-course radiotherapy, 128 to short-course radiotherapy with delay, and 128 to long-course radiotherapy with delay, and 455 patients in the two-arm randomisation, of whom 228 were randomly assigned to short-course radiotherapy and 227 to short-course radiotherapy with delay. In patients with any local recurrence, median time from date of randomisation to local recurrence in the pooled short-course radiotherapy comparison was 33·4 months (range 18·2–62·2) in the short-course radiotherapy group and 19·3 months (8·5–39·5) in the short-course radiotherapy with delay group. Median time to local recurrence in the long-course radiotherapy with delay group was 33·3 months (range 17·8–114·3). Cumulative incidence of local recurrence in the whole trial was eight of 357 patients who received short-course radiotherapy, ten of 355 who received short-course radiotherapy with delay, and seven of 128 who received long-course radiotherapy (HR vs short-course radiotherapy: short-course radiotherapy with delay 1·44 [95% CI 0·41–5·11]; long-course radiotherapy with delay 2·24 [0·71–7·10]; p=0·48; both deemed non-inferior). Acute radiation-induced toxicity was recorded in one patient (<1%) of 357 after short-course radiotherapy, 23 (7%) of 355 after short-course radiotherapy with delay, and six (5%) of 128 patients after long-course radiotherapy with delay. Frequency of postoperative complications was similar between all arms when the three-arm randomisation was analysed (65 [50%] of 129 patients in the short-course radiotherapy group; 48 [38%] of 128 patients in the short-course radiotherapy with delay group; 50 [39%] of 128 patients in the long-course radiotherapy with delay group; odds ratio [OR] vs short-course radiotherapy: short-course radiotherapy with delay 0·59 [95% CI 0·36–0·97], long-course radiotherapy with delay 0·63 [0·38–1·04], p=0·075). However, in a pooled analysis of the two short-course radiotherapy regimens, the risk of postoperative complications was significantly lower after short-course radiotherapy with delay than after short-course radiotherapy (144 [53%] of 355 vs 188 [41%] of 357; OR 0·61 [95% CI 0·45–0·83] p=0·001). Interpretation: Delaying surgery after short-course radiotherapy gives similar oncological results compared with short-course radiotherapy with immediate surgery. Long-course radiotherapy with delay is similar to both short-course radiotherapy regimens, but prolongs the treatment time substantially. Although radiation-induced toxicity was seen after short-course radiotherapy with delay, postoperative complications were significantly reduced compared with short-course radiotherapy. Based on these findings, we suggest that short-course radiotherapy with delay to surgery is a useful alternative to conventional short-course radiotherapy with immediate surgery. Funding: Swedish Research Council, Swedish Cancer Society, Stockholm Cancer Society, and the Regional Agreement on Medical Training and Clinical Research in Stockholm.